IoT-based Flower Garden Care System using the ESP8266 Wi-Fi Module and Telegram Application / Syahida Atirah Che Omar, Rashidah Ramle - Che Omar, Syahida Atirah; Ramle, Rashidah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Proper care is very important to keep a flower garden in good condition, whether it is getting enough water or ensuring the safety of the flower garden area. Using technology can have advantages for people who have a small flower garden at home. The IoT-based Flower Garden Care System using the ESP8266 Wi-Fi Module and Telegram Application is developed to solve the problems of people always forgetting to water it and for the safety of the flower garden area from animal harm. This research was uses an ESP8266 Wi-Fi module, a Telegram application, and two sensors, which are a PIR motion sensor and a soil moisture sensor. The development process for this research follows six stages, which are initiation, planning, design and development, implementation and testing, data analysis, and documentation. The aims of this research are to develop a prototype on an IoT system for a flower garden to monitor using sensors, a Wi-Fi module, and a Telegram application and evaluate the prototype performance using functionality testing.